The relevance of Tafsīr al-Jalālayn among the Muslims of Malabar - Kunnakkadan, Muhammed Unais; Ahmad, Nadzrah; Abdo Khaled, Nashwan (IIUM Press, International Islamic University Malaysia, 2020)
Tafsīr al-Jalālayn is one of the renowned exegeses of the Qurʿan since the 15th century. Thanks to its authentic interpretation and smaller size, it could garner more recognition in the Muslim world. The academic impact it made at the Malabar province of south India is an exciting fact unveiled yet. According to this particular region’s long Islamic heritage and close relations with Arabs from an early time, such specific studies are much more significant. A qualitative approach based upon an extensive review of literature has been used to analyze the scholarly written contributions in this regard. This article mainly describes the latest four Arabic commentary works and two translations of Tafsīr al-Jalālayn‎ penned by scholars of the region. Its place in the prominent curriculums of higher secondary Madrasa systems, conventional Palli Darses and Islamic institutions, in addition to several published editions are compared through field study. The participant observation helped to note its relevance in both religious and theological spheres. The study also provides historical data related to the regional socio-religious growth of the Muslim Mappila community of Malabar.